2019
DOI: 10.1007/s40430-019-1832-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of abrasive wear by rice husk of an HVOF WC–Co–Cr-based coating and an electric arc sprayed coating based on Fe–Cr–B–Si

Abstract: The effect of abrasive wear is particularly relevant in the industrial areas of agriculture, mining, mineral processing and earth moving. Wear problems occur in mills and silos where grain is stored and moved in large quantities through the process of agro-processing. Machines and equipment that work under direct contact with the grain suffer from severe three-body abrasive wear from the rice husks. The main objective of this study was to investigate the abrasive wear behavior of an Fe-29Cr-4B-1.75Si coating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…It should be noted that the ridges formed do not slide in one direction; particles are being pushed against the surface and they slide in different directions, and the grooves intersect as seen in Figure 13a. The hardness of the Ni-P-Tribaloy coating also contributes to its wear resistance, as studies have shown that the penetration depth on the worn surface by the abrasive particles is proportional to the ratio of hardness to applied force [34,35]. Furthermore, there is also compaction that occurs, along with plowing, arising from the applied load and the contact between the rough surface and the rubber, where the material is pressed in by that contact.…”
Section: Wear Scar Analysismentioning
confidence: 99%
“…It should be noted that the ridges formed do not slide in one direction; particles are being pushed against the surface and they slide in different directions, and the grooves intersect as seen in Figure 13a. The hardness of the Ni-P-Tribaloy coating also contributes to its wear resistance, as studies have shown that the penetration depth on the worn surface by the abrasive particles is proportional to the ratio of hardness to applied force [34,35]. Furthermore, there is also compaction that occurs, along with plowing, arising from the applied load and the contact between the rough surface and the rubber, where the material is pressed in by that contact.…”
Section: Wear Scar Analysismentioning
confidence: 99%